Potential risk factors of brucellosis in dairy farmers of peri-urban areas of South West Delhi - Navita Yadav; Divya Aggarwal (Wolters Kluwer Medknow Publications, 2020)
Background: Brucellosis is a bacterial disease caused by various Brucella species, which mainly infect cattle, swine, goats, sheep, and dogs. Humans generally acquire the disease through direct contact with infected animals, by eating or drinking contaminated animal products, or by inhaling airborne agents. The majority of cases are caused by ingesting unpasteurized milk or cheese from infected goats or sheep. Objective: The objective of the study was to identify the exposure to potential risk factors of brucellosis among the dairy farmers of South West Delhi. Materials and Methods: This cross-sectional study was carried out in Jhuljhuli village of Najafgarh division in South West Delhi from January 2017 to April 2017. One hundred individuals were selected through snowball sampling method. A semistructured questionnaire was designed to conduct interviews for data collection. Results: On analysis, it was found that only 36% of the respondents get their animals vaccinated regularly. Regarding the treatment of the animals, 70% of the individuals said that they treat their animals on their own. 72% of the individuals' animals had cases of abortion in the last 1 year. 100% of the respondents reported assisting their animals during reproduction without using any protective gear. Almost half (57%) of the respondents consumed raw milk at their home on different occasions. Conclusions: The study concluded in bringing out the contributing risk factors for brucellosis. The study concluded that treating animal infection on their own and helping animals during reproduction without using protective gear, as major contributing risk for brucellosis. Other factors includes, keeping animals in close proximity during sleep, irregular vaccination, etc.